1991
DOI: 10.1620/tjem.164.237
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Stem Blood Flow under Various Grades of Brain Stem Ischemia.

Abstract: This report describes a study of brain stem blood flow (BBF) change under various grades of brain stem ischemia in a new experimental rat model. The main damage was caused by occlusion of the median and paramedian perforating arteries of the basilar artery. In this model, hyperperfusion was generally observed in cases of mild or moderate ischemia within 1 hr after recirculation and lasted for approximately 1 hr. During hyperperfusion, BBF increased to over 60 ml/100 g brain/min and was significantly greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
4
0
2
Order By: Relevance
“…A decreased VR to acetazolamide was shown in an animal model, where the median and paramedian branches of the BA were occluded [26]. In our study BLI patients showed a slight, insignificant decrease of the RVC.…”
Section: Discussionsupporting
confidence: 65%
“…A decreased VR to acetazolamide was shown in an animal model, where the median and paramedian branches of the BA were occluded [26]. In our study BLI patients showed a slight, insignificant decrease of the RVC.…”
Section: Discussionsupporting
confidence: 65%
“…The mechanism by which the inhibition of 20-HETE synthesis prevents the observed hyperperfusion following cerebral ischemia in SHR and SHRSP cannot be determined by the present results. However, 20-HETE has recently been shown to stimulate formation of ROS by interactions with NADPH oxidase and uncoupling of NO synthase (NOS) (4,39,62), and there is evidence that the phenomenon of postischemic hyperperfusion may be associated with impairment of vascular reactivity by the elevated production of ROS in cerebral ischemia and reperfusion (27,34,48,58). This suggests that the effect of the 20-HETE inhibitor on postischemic cerebral hyperperfusion and on infarct size in SHR and SHRSP may be due to a reduction in cerebral ROS production, which may in itself be neuroprotective, and also may reduce secondary neural damage associated with vascular leakage and cerebral edema and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperperfusion occurring in the brainstem is rare 1,2 . Brainstem hyperperfusion as a result of intravenous thrombolysis has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperperfusion occurring in the brainstem is rare. 1,2 Brainstem hyperperfusion as a result of intravenous thrombolysis has not been reported. Intravenous thrombolytic therapy with recombinant tissue plasminogen activator (rtPA) is currently the only approved treatment for acute ischemic stroke when given within 3 hours after the stroke onset.…”
Section: Introductionmentioning
confidence: 99%